Multifrequency Wilkinson power divider using microstrip nonuniform transmission lines - Khalaj-Amirhosseini, M.; Moghavvemi, M.; Ameri Mahabadi, H. (2011)
A new idea is proposed to modify the conventional Wilkinson power dividers to operate at two or several desired frequencies. The proposed structure contains two Microstrip Nonuniform Transmission Lines (MNTLs) instead of two uniform ones with nearly the same length at the minimum frequency. The strip width of MNTLs is considered variable and is written as a truncated Fourier series. Three nonuniform power dividers are designed and one of them operating at frequencies 1.0, 2.8, and 4.5 GHz is fabricated and measured. The measured results of the fabricated diplexer have a good agreement with the theoretical results.